Phytochemical characterization and biological activities of green tea (Camellia sinensis) produced in the Azores, Portugal - Sérgio Barreira; Carla Moutinho; André M.N. Silva; José Neves; Ean-Jeong Seo; Mohamed-Elamir F. Hegazy; Thomas Efferth; Lígia Rebelo Gomes (Elsevier, 2021)
Background: Green tea is not only one of the most widely consumed beverages worldwide, but is also known for its health promoting and therapeutic effects. Green tea is cultivated in areas with high humidity and acidic soils in China, Indonesia and Japan. Those places have well-marked dry and rainy seasons. In opposite, Azores have a climate with constant average annual rainfall and, unlike eastern regions, relatively constant air humidity throughout the year. While a brand implemented on the Portuguese market, the quality of green tea produced in Azores must be guaranteed. Quality control measures based on phytochemical determination of the chemical composition and biological activities are needed in order to address whenever climate changes interferes significantly with composition and biological effects. Purpose: Make the phytochemical characterization of various extracts of green tea leaves coming from Azores and evaluate the anti-cancer activities of the extracts in order to compare the obtained results with those of teas coming from eastern regions. Methods: Phytochemical characterization (catechins, oxyaromatic acids, flavonols, alkaloids and theanine) and total catechins contents (TCC) was performed by using HPLC-DAD analysis, in infusions (5-7 min and 30 min), maceration and methanolic extracts of Camellia sinensis samples coming from Azores, Portugal. The antioxidant activity of extracts was measured by the DPPH assay and the total phenolics contents (TPC) were estimated using the Folin-Ciocalteu colorimetric method. The cytotoxic activity towards drug sensitive and multidrug-resistant leukemia cell lines was determined by the resazurin assay. Results: The TCC was higher in methanolic extracts and lower in maceration, as epigallocatechin gallate (EGCG) and epicatechin gallate (ECG) concentrations were significantly higher in methanolic extracts and were only residual in maceration extracts. Maceration extracts showed the highest content of gallic acid, indicating that methanol extracts contained more flavonols of higher molecular weight and/or that maceration may lead to the degalloylation of catechins. The amount of o-caffeoylquinic acid extracted was significantly higher in methanolic samples. Short-term extraction at high temperatures resulted in high amounts of neochlorogenic acid. The contents of glycosylated quercitin-3-d-galactoside and kaempferol-3-glucoside were small in maceration samples and high in methanolic samples. Caffeine was easily extracted by methanol (99%) compared with water, while extraction of the amino-acid l-theanine was unattainable with methanol. TPC values correlated linearly with DPPH• IC50, with infusion samples showing the best antioxidant capacities. The aqueous and the methanol/water extracts were active in multidrug-resistant and drug sensitive cancer cells. Conclusion: Despite these climatic differences, the phytochemical characterization revealed that tea coming from the Azores compares well with those from China and Japan. In addition, tea can be produced without fungicides and pesticides to control pests that appear during rainy seasons. This allows the production of high-quality bioorganic tea. Aqueous and methanol/water extracts of the Azorean tea showed to be useful targeting sensitive and drug-resistant tumor cells.